(untitled) (Ameghiniana, 2018)
The early late Tremadocian (Tr2) interval is exceptionally well-represented in eastern areas of the Argentine Cordillera Oriental. New field collections and detailed taxonomic reassessments, as well as a reevaluation of regional data, permit the development of a highly resolved trilobite-based biostratigraphic framework. The concept of the traditional Bienvillia tetragonalis biozone is emended and the new Asaphellus nazarenensis biozone is proposed. Hence, the Tr2 interval encompasses a succession of four trilobite biozones including in ascending order the Kainella teiichii, the Bienvillia tetragonalis, the Asaphellus nazarenensis, and the Notopeltis orthometopa biozones. This resolution is notably higher than that provided by biostratigraphically significant groups such as graptolites and conodonts, and allows a detailed basinwide correlation. New taxonomic information on A. nazarenensis Tortello and Esteban and N. orthometopa (Harrington), is provided and the new species Asaphellus albae sp. nov. is defined. Detailed correlation of the trilobite fauna from the Tr2 interval with that of other paleocontinents is difficult. Taxa are mostly endemic or display wide geographic distributions but with long stratigraphic ranges. Overall, both trilobite-based and indirect international correlations highlight that this interval is hardly recognized, incompletely preserved, or the trilobite fauna is poorly known in most areas of Gondwana. Consequently, due to the completeness of the stratigraphic and fossil records of the Tr2 in the Cordillera Oriental, this region represents a global reference site for the study of this interval.